Disulfiram Induced Psychosis: A Case Report - Survilaitė, D. R.; Žemaitytė, R. (Neurologijos seminarai, 2024)
Introduction. Disulfiram is one of three medications approved by the Federal Drug Administration (FDA) to treat alcohol dependence. Patients tend to abstain from alcohol to avoid the unpleasant effects of alcohol toxicity. There may be some side effects, the most common of which are drowsiness, unusual tiredness, headache, metallic taste in mouth, skin rashes, decreased libido. Disulfiram induced psychosis is a psychiatric side effect that occurs very rarely. Case report. We report the case of a 33-year-old patient with nearly 15 years history of psychiatric personality disorder and alcohol dependence. Approximately 4 days of alcohol abstinence, as an inpatient he was administered disulfiram. After two weeks, the patient began to feel some side effects. He was admitted to hospital and was diagnosed with disulfiram induced psychosis. Discussion. The effect of disulfiram on alcohol metabolism was noticed in the 1940s. It should be used only by motivated patients who must be fully informed about the alcohol-disulfiram reaction. Disulfiram should only be started after about 10 days of sobriety, and the recommended dosage is 500 mg/day. The drug should be used with caution in people with a history of heart disease, diabetes mellitus, hypothyroidism, cerebral damage, nephritis, liver cirrhosis, epilepsy. Caution is recommended for patients who use benzodiazepines, some antibiotics, anticoagulants, tricyclic antidepressants. There may be some adverse effects, more serious ones include changes in vision, numbness, pain or weakness in the limbs, liver cell damage, peripheral neuropathy, seizures – but these are considered to be very rare. Psychiatric side effects may include mood changes, psychotic reactions, memory impairment. Reliable data is lacking, but cases of disulfiram induced psychosis are considered to be rare. Patients taking disulfiram should be monitored carefully.